Electronic structure of AgCd2GaS4 - Tretyak, Alina; Bulatetska, Lesya; Bekenev, Valeriy; Parasyuk, Oleg; Khyzhun, Oleg; Bozhko, Volodymyr; Божко, Володимир; Третяк, Аліна; Булатецька, Леся; Бекеньов, Валерій; Парасюк, Олег; Хижун, Олег (Східноєвропейський національний університет ім. Лесі Українки, 2013)
In the present work we report on measurements of X-ray photoelectron (XP) valence-band spectrum including the comparatively wide energy region corresponding to location of upper core-levels (up to ~80 eV with respect to the bottom of the valence band) of the atoms constituting a quaternary AgCd2GaS4 single crystal grown by the Bridgman method. Electronic structure of AgCd2GaS4 are also theoretically studied by using the first-principles full potential linearized augmented plane wave (FP-LAPW) method. The FP-LAPW method has been employed in the present work to calculate binding energies of upper core-levels for the AgCd2GaS4 compound. With respect to values of binding energies of the Cd 4p, Ag 4p and Ga 3d core-levels, the theoretical and experimental data for the AgCd2GaS4 compound were found to be in agreement to each other. Curves of dominant partial densities of states of AgCd2GaS4 have been compared on a common energy scale with the XP valence-band spectrum of the compound under consideration. ; Рентгенівський фотоелектронний (РФ) спектр валентних електронів монокристалу AgCd2GaS4, вирощеного методом Бріджмена, досліджено в широкому енергетичному інтервалі, котрий уключав спектри внутрішніх електронів, розміщені на відстані аж до ~80 еВ від нижнього краю валентної зони. Електронна структура сполуки AgCd2GaS4 також розрахована «з перших принципів» методом приєднаних плоских хвиль – повного потенціалу (ППХ-ПП). Величини енергій зв’язку (Езв) внутрішніх Cd4p-, Ag4p- i Ga3d-електронів, що отримані теоретично для AgCd2GaS4 за допомогою ППХ-ПП методу, добре збігаються з експериментальними значеннями Езв, котрі виміряні для досліджуваного кристала за допомогою РФ-спектроскопії. Виконано суміщення кривих парціальних щільностей станів складових атомів сполуки AgCd2GaS4 у єдиній енергетичній шкалі з РФ-спектром валентних електронів.
Електронна структура AgCd2GaS4
Keywords: AgCd2GaS4; Electronic structure; First-principles band-structure calculations; X-ray photoelectron spectroscopy; densities of states; AgCd2GaS4; електронна структура; розрахунок електронної структури з перших принципів; рентгенівська фотоелектронна спектроскопія; щільність станів